Relationship Between Attitudes, Academic Performance, Gender and Choice of Agricultural Careers Among Secondary School Students in Kanungu District Uganda. - Byaruhanga, Hillary (Kabale University, 2024)
The aim of this study was to explore the relationship between attitudes, academic performance, gender, and the choice of agricultural careers among secondary school students in Kanungu District, Uganda. The study focused on specific objectives, including examining the relationship between students' attitudes towards agriculture and their choice of agricultural careers, investigating how agricultural academic performance influences the choice of agricultural careers, and exploring the connection between students' attitudes towards agriculture and their agriculture scores. A descriptive research design was used, employing both qualitative and quantitative methods. Using simple random and purposive sampling, 291 respondents were selected for participation. Data were collected through questionnaires and interviews. The findings revealed that most students were unsure about whether those with a favorable view of agriculture are more likely to pursue agricultural careers, with a mean score of 3.29 and a standard deviation of 0.548, indicating that students were generally "not sure" about this relationship. The study found a significant positive correlation (Spearman's rho = 0.506**, p < 0.01) between students' attitudes towards agriculture and their choice of agricultural careers. However, most respondents disagreed that experiential learning influenced their agricultural academic performance and career choice, with a mean score of 2.41 and a standard deviation of 1.082. The role of mentorship and positive role models was also assessed, with a mean score of 2.47 (SD = 0.922). Additionally, no significant relationship was found between students' attitudes towards agriculture and their agricultural scores (p = 0.249, r = 0.142), as the p-value was greater than 0.05. The study concludes that schools should implement programs to enhance students' attitudes toward agriculture, such as integrating modern agricultural practices and technologies into the curriculum.